An Analysis of Conflict of The Main Character in Whiplash Movie by Damien Chazelle - Ramdani, Lalu Alfin Maulana; Nuriadi, Nuriadi; Fitriana , Eka (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2023)
Movie is included in drama as a form of literature. The story is told in the dialogue, the forms of film and drama were identical. In addition, the objective of this study was to examine the conflicts encountered by the main character and to analyze the impacts of these conflicts in the Whiplash movie by Damien Chazelle. The research was supported by Kenney and Aruna's conflict theory. The research used a qualitative approach. The data extracted from the Whiplash movie, including dialogues, sentences, words, and phrases. It was found that there were two types of conflicts experienced by the main character in the Whiplash Movie: internal and external conflicts. Moreover, the study revealed two consequences resulting from these conflicts, both positive and negative impacts were observed. For instance, averts further serious conflict, results in personal communal change, brings two or more parties, always in state of tension, feelings of resentment and hatred escalate, and other relationships also are affected. Furthermore, the study identified psychological and sociological impacts arising from the conflicts faced by the main character, including experiences of trauma, anxiety, and depression. Meanwhile, the sociological conflicts encompassed clashes between individual and authority, as well as issues of competition and collaboration.